2017
DOI: 10.4236/ad.2017.51003
|View full text |Cite
|
Sign up to set email alerts
|

Amalgamation and Small-Scale Gold Mining at Ancient Sardis, Turkey

Abstract: In the ancient world gold was mined mainly from alluvial occurrences using gravity methods combined with the use of mercury (amalgamation), a method that is still used today in small-scale alluvial gold mines worldwide. Cyanide, which was first used in the 1880s, is used in large-scale hardrock mines to recover gold, silver, copper, and other metals from porphyry and disseminated ore deposits. Therefore, amalgamation must be considered, or specifically in the case of Sardis, reconsidered as the technology for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These vapors are an important source of inhalational Hg toxicity from ancient times and the metallic form is released into the rivers and carried downstream, becoming another major source of toxicity. 18,19 Aquatic ecosystem and marine food chain are getting affected by the toxic waste of Hg even today. The Global Mercury Assessment 2018 (GMA 2018) conducted by the United Nations has shown that artisanal and small-scale gold mining (ASGM) (37.7%), stationary combustion of fossil fuel and biomass, especially coal (21%), nonferrous metals production (15%), and cement production (11%) are currently the four main sources of Hg emission.…”
Section: Human Exposure To Mercurymentioning
confidence: 99%
“…These vapors are an important source of inhalational Hg toxicity from ancient times and the metallic form is released into the rivers and carried downstream, becoming another major source of toxicity. 18,19 Aquatic ecosystem and marine food chain are getting affected by the toxic waste of Hg even today. The Global Mercury Assessment 2018 (GMA 2018) conducted by the United Nations has shown that artisanal and small-scale gold mining (ASGM) (37.7%), stationary combustion of fossil fuel and biomass, especially coal (21%), nonferrous metals production (15%), and cement production (11%) are currently the four main sources of Hg emission.…”
Section: Human Exposure To Mercurymentioning
confidence: 99%
“…The metal would have been used for gilding and alluvial gold amalgamation (Barnes & Bailey, 1972;Brooks et al 2017). Fine-grained gold from the Takht-e Soleyman mining district, northwest Iran, was first panned and then mixed with mercury for retorting (Momenzadeh et al, 2016).…”
Section: History Of Retorting and Ancient Industrial Usesmentioning
confidence: 99%
“…However, owing to the imperfections in the ancient ceramics or in the seals between the ceramic vessels, then this process would have released Hg fumes, along with SO 2 , from the retorts or up the chimney (Brooks et al 2017). Any of the pink-to light-red calcined material resulting from retorting may have been plowed under, covered by jungle growth, debris flows, or removed by rainfall.…”
Section: Human Healthmentioning
confidence: 99%
“…The ore of mercury, cinnabar (HgS), is a sulfide mineral that was widely used in the ancient world: 1) it was mined, selectively ground, and widely used as a blood-red pigment (vermilion) on ceramics, gold masks, murals, statues, burial rites (Petersen, 1970(Petersen, /2010Bonavia, 1985;Brooks et al, 2008;Spindler, 2018) and, 2) it was retorted to produce mercury (Cabrera la Rosa, 1954;Craddock, 1995;Brooks, 2012). Retorting cinnabar to obtain mercury has been documented more than 8000 years ago in ancient Türkiye (Barnes & Bailey, 1972;Brooks et al, 2017); during Roman time (Pliny the Elder, 77 AD); the Middle East (Al-Hassan & Hill, 1986), in ancient Mexico (Langenscheidt, 1986); medieval Europe (Agricola, 1556(Agricola, /1912; California in the 1840s (Bailey & Everhart, 1964); and present-day Indonesia (Paddock, 2019). Mercury has been used to recover gold by amalgamation with mercury for centuries (Ahern, 2016;Fernández-Lozano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%